Peningkatan Motivasi dan Hasil Belajar Murid Kelas VIII Melalui Media Game Edukatif Quizizz Mode Kertas pada Mata Pelajaran IPS di SMPN 13 Madiun - Motik, Fahmi; Sudarmiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This classroom action research addresses low student motivation and learning outcomes in Social Studies at SMPN 13 Madiun, where traditional teaching methods resulted in monotonous learning experiences. The study aims to describe the implementation process, examine motivation improvement, and assess learning outcome enhancement through Quizizz Mode Kertas educational game media. Employing collaborative classroom action research over two cycles from June to November 2025, this study involved 32 eighth-grade students. Data collection utilized observation, documentation, and tests, analyzed through quantitative and qualitative approaches. Findings reveal significant improvements: student motivation increased from 47% (moderate) in Cycle I to 68% (high) in Cycle II, a 21% enhancement. Learning activity progressed from adequate (11.09) to good (16.84). Classical completeness improved dramatically from 46.9% pre-cycle to 63% in Cycle I, reaching 84% in Cycle II, surpassing the 80% target. Quizizz Mode Kertas effectively creates dynamic, interactive learning while maintaining gamification elements without requiring personal digital devices. Recommendations include broader implementation across subjects, improved time management, difficulty adjustments, institutional support, and further research in diverse contexts to maximize learning quality.